Factors influencing the development of ecotourism in tourist towns in Kermanshah Province, Iran - Moradi, Heshmat; Poursaeed, Alireza; Vahedi, Marjan; Bagher Arayesh, Mohammad (Revista de la Universidad del Zulia, 2020)
This study was carried out to explain the development of ecotourism in the tourist villages of the Kermanshah province, using a quantitative-qualitative method. Qualitative data analysis was performed using the maxqda12 software. The statistical sample in the qualitative section was snowball and 20 experts. In the quantitative section, the stratified random sampling method with the Morgan ratio was used. The research tool was an interview with a questionnaire prepared by an investigator derived from the qualitative phase of the research and the background. Data analysis with SPSS24 and PLS2 software indicated that the study model was adequate. On the other hand, it was discovered that all the dimensions of the conceptual research model were extracted from the qualitative and literary studies of the research literature to measure the factors and had a good function in the measurement of these concepts. The multivariate determination coefficient for the main structural equation was 85.5%, indicating that the independent variables of the study included economic, social, and cultural factors, participation, attractions, management, policy formulation, and infrastructure factors. Economic, social and cultural factors, attractions, ecotourism, participatory management and policy-making infrastructures have priorities, second to seventh, respectively. The first priority focuses on anticipating changes in the development of ecotourism.